Заболевания сердечно-сосудистой системы у спортсменов. - Зиневич, Я. В.; Левон, М. М.; Шматова, Е. А.; Zinevich, J. V.; Levon, M. M.; Shmatova, E. A. (Східноєвропейський національний університет імені Лесі Українки, 2012)
Современный спорт высоких достижений – это сфера деятельности, в которой организм спортсмена подвергается экстремальным и психологическим нагрузкам. Патология сердечно-сосудистой системы у спортсменов занимает одно из первых мест в структуре их общей заболеваемости. Modern sport of high achievements is a sphere of activity in which the organism of sportsman is exposed to the extreme and psychological loads. Pathology of the саrdiо-vascular system for sportsmen occupies one of the first places in the structure of their general morbidity.
Diseases of the Cardio-Vascular System in Athletes.
Keywords: спорт; сердечно-сосудистая система; sports; cardio-vascular system